Genetic Diversity and Principle Component Analyses for Fodder Yield and their Component Traits in Genotypes of Forage Sorghum (Sorghum bicolor L. Moench) - Jain, S K; Patel, P R (Annals of Arid Zone, 2016)
In the current set of an experiment twenty eight forage sorghum genotypes including two checks were evaluated for understanding genetic diversity for fodder yield and their component traits in forage sorghum. For evaluation of these traits, correlation, principal component (PC) and diversity analysis employed to obtain suitable parents that can be exploit for further breeding programs. Green and dry fodder yield was significantly and positively correlated with stem girth, leaf width, leaf length, number of leaves/plant, plant height and days to 50% flowering. The positive correlation among these fodder yield contributing traits suggested that these traits are important for direct selection of high fodder yielding genotypes. By performing analysis for PCs it was observed that variance for Eigen value was maximum (3.844) in PC-1 followed by PC-II (1.455) and least for PC-III (1.076). First three PC scored 70.89% variation and variance percentage was maximum in PC-I (42.72%) followed by PC-II (16.17%) and PC-III (11.97%). The total variation was mainly due to variation in the fodder yield and their contributing traits i.e. green fodder yield, dry fodder yield, stem girth, leaf width, number of leaves/plant, leaf length, and days to 50% flowering. The twenty eight genotypes were grouped into four clusters on the basis of average linkage. Cluster-I contained 3 genotypes, cluster-II contained 9 genotypes, cluster-III contained 14 genotypes and cluster-IV contained 2 genotypes. Distribution pattern of all the genotypes into four clusters showed the presence of considerable genetics diversity among the genotypes for most of the traits under consideration. Varieties of cluster first and second was superior in terms of green and dry fodder yield, third cluster for early maturity and forth for brix per cent and these genotypes can use as release new cultivar and for further breeding programs